Design and Build a Virtual Reality Based Cycling Simulator Game - Sesarius Satria Lintang Mahendra; Erdhi Widyarto Nugroho; FX. Hendra Prasetya (Journal of Business and Technology, 2023)
At the present time, there is a lot of digitalization being carried out. The current busy work also often makes people need to carry out an activity without leaving the place. One of them is exercising, in this case is cycling.Therefore, an idea emerged to design a VR-based cycling simulator game. The purpose of this study is to find out how the interaction between cycling and VR is, and to find out the interesting points of this game and its use as a new alternative to cycling. The method used in this study was to test the "Simulator Sepeda VR" game on several users and collect data through interviews. The results of this study indicate that the "Simulator Sepeda VR" game is able to provide an interesting experience and can also be an alternative for cycling at home.